Arc length control for efficiency enhancement of energy usage in plasma dry reforming process. (December 2018) - Khoe Dinh, Duy; Lee, Dae Hoon; Song, Young-Hoon; Jo, Sungkwon; Kim, Kwan-Tae
Highlights: Experiment and analysis on possible control of efficiency of energy usage in plasma process are introduced. Arc length can be controlled effectively in novel rotating arc reactor. Different arc length results in different electrical and thermal characteristics. Arc length elongation enhanced heat transfer to gases and reduced conduction heat loss to reactor body at a given power. The firm physical basis for further optimization of the arc process for the chemical reaction is obtained. Abstract: Arc plasma has been applied in diverse reactions because it can provide the mechanism for highly thermal activations. However, the efficiency of conversion from electrical energy to thermal energy for the reactant is not sufficiently high, resulting in challenges in practical applications of the arc in various chemical processes. In this study, a method is introduced to enhance the energy usage efficiency for the reactant. The enhancement is based on the control of the arc length elongation. An increase in the arc length results in an enhanced heat transfer from the arc column to the reactant, followed by the reduction of the conductive heat loss to the reactor body. The existing DC arc technologies cannot easily extend the arc length because of the arc instability. However, in this study, a novel AC arc technology was adopted that can support a stable arc with a sufficiently elongated length. Correspondingly, a comparative study on different arc lengths was conducted for the dry reforming (as a model reaction). The increased arc length results in an enhanced heat transfer to the gas or a higher gas temperature. This is followed by the enhancement of the conversions of the reactants for the same supplied electric power. The results provide a firm physical basis for further optimizations of the arc process for chemical reactions.